2003
DOI: 10.1097/00024382-200301000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptor Antagonists Modulate Ca2+-Activated K+ Channels in Mesenteric Arterial Smooth Muscle Cells of Rats in Hemorrhagic Shock

Abstract: Previous study has indicated a significant enhancement of activity of large-conductance Ca2+-activated K+ channel (BKCa) in mesenteric arterial vascular smooth muscle cells isolated from rats in vascular hyporesponsive stage of hemorrhagic shock. In the present study, the effect of opioid receptor antagonism on BKCa activity in the vascular smooth muscle cells of rats in the hyporesponse stage of hemorrhagic shock was investigated by using inside-out configuration of the patch-clamp technique. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Studies have shown that the vascular reactivity to vasoconstrictors and vasodilators can be reduced greatly after severe trauma or shock [1][2][3][4][5][6][7]. Many factors, including desensitized adrenoceptors [1,8], nitric oxide (NO) [3, 7, 9 -13], endogenous opioid peptides [4,14], inflammatory cytokines such as TNF␣ [15,16] and IL-1 [17] have been proposed to be involved in the development of vascular hyporeactivity during shock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the vascular reactivity to vasoconstrictors and vasodilators can be reduced greatly after severe trauma or shock [1][2][3][4][5][6][7]. Many factors, including desensitized adrenoceptors [1,8], nitric oxide (NO) [3, 7, 9 -13], endogenous opioid peptides [4,14], inflammatory cytokines such as TNF␣ [15,16] and IL-1 [17] have been proposed to be involved in the development of vascular hyporeactivity during shock.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, including desensitized adrenoceptors [1,8], nitric oxide (NO) [3, 7, 9 -13], endogenous opioid peptides [4,14], inflammatory cytokines such as TNF␣ [15,16] and IL-1 [17] have been proposed to be involved in the development of vascular hyporeactivity during shock. This vascular hyporeactivity may also play an important role in the development and the outcome of the shock state, and can interfere with the therapy of shock by reducing the effectiveness of vasoactive agents [1].…”
Section: Introductionmentioning
confidence: 99%
“…In VSMCs, freeCaM binding with Ca 2+ could accelerate the formation of the CaM-CaM related kinase II (CaMK II) complex, a ubiquitous multifunctional serine/threonine kinase expressed in VSMCs as multimers of γ-and/or δ-sun units [29] , and increase MLCK activity and MLC20 phosphorylation, which contribute to vascular contraction [30] . However, Ca 2+ release located next to cytomembranes, also known as Ca 2+ spark, triggers the formation of STOCs [31] and activates the large conductance calcium activated potassium channel (BK Ca ), which at least partially contributes to the vascular hyporeactivity observed after hemorrhagic shock [32] . However, more research is required to determine whether the over-activation of RyR2-mediated Ca 2+ release during the early stage after hemorrhagic shock is coupled with the activation of CaM-CaMK II signal cascade and vascular hyperreactivity or whether the over-activation of RyR2-mediated Ca 2+ release during the late stage after hemorrhagic shock is linked to the BK Ca -dependent signaling pathway and the occurrence of vascular hyporeactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced vascular reactivity plays an important role in the development and outcome of the shock state. Vascular hyporesponsiveness may be related to the desensitization of adenoreceptor, the increase of nitric oxide (NO), the functional disorder of the K + and Ca 2+ channels in VSMC and the hyperpolarization of the cell membrane [13,14]. Our previous study has shown that calcium desensitization existed in VSMC following shock may contribute to the occurrence of vascular hyporeactivity [9].…”
Section: Discussionmentioning
confidence: 99%